A controlled pilot trial of two commercial video games for rehabilitation of arm function after stroke. (July 2015) - Chen, Mei-Hsiang; Huang, Lan-Ling; Lee, Chang-Franw; Hsieh, Ching-Lin; Lin, Yu-Chao; Liu, Hsiuchih; Chen, Ming-I; Lu, Wen-Shian
Objectives: To investigate the acceptability and potential efficacy of two commercial video games for improving upper extremity function after stroke in order to inform future sample size and study design. Design: A controlled clinical trial design using sequential allocation into groups. Setting: A clinical occupational therapy department. Subjects: Twenty-four first-stroke patients. Interventions: Patients were assigned to one of three groups: conventional group, Wii group, and XaviX group. In addition to regular one-hour conventional rehabilitation, each group received an additional half-hour of upper extremity exercises via conventional devices, Wii games, or XaviX games, for eight weeks. Main measures: The Fugl-Meyer Assessment of motor function, Box and Block Test of Manual Dexterity, Functional Independence Measure, and upper extremity range of motion were used at baseline and postintervention. Also, a questionnaire was used to assess motivation and enjoyment. Results: The effect size of differences in change scores between the Wii and conventional groups ranged from 0.71 (SD 0.59) to 0.28 (SD 0.58), on the Fugl-Meyer Assessment of motor function ( d  = 0.74) was larger than that between the XaviX and conventional groups, ranged from 0.44 (SD 0.49) to 0.28 (SD 0.58) ( d  = 0.30). Patient enjoyment was significantly greater in the video game groups (Wii mean 4.25, SD 0.89; XaviX mean 4.38, SD 0.52) than in the conventional group (mean 2.25, SD 0.89, F = 18.55, p  < 0.001), but motivation was not significantly different across groups. Conclusion: Patients were positive to using video games in rehabilitation. A sample size of 72 patients (24 per group) would be appropriate for a full study.